Alzheimer's disease biomarker discovery using SOMAscan multiplexed protein technology. Issue 6 (28th April 2014) - Sattlecker, Martina; Kiddle, Steven J.; Newhouse, Stephen; Proitsi, Petroula; Nelson, Sally; Williams, Stephen; Johnston, Caroline; Killick, Richard; Simmons, Andrew; Westman, Eric; Hodges, Angela; Soininen, Hilkka; et al.
Abstract: Blood proteins and their complexes have become the focus of a great deal of interest in the context of their potential as biomarkers of Alzheimer's disease (AD). We used a SOMAscan assay for quantifying 1001 proteins in blood samples from 331 AD, 211 controls, and 149 mild cognitive impaired (MCI) subjects. The strongest associations of protein levels with AD outcomes were prostate‐specific antigen complexed to α1‐antichymotrypsin (AD diagnosis), pancreatic prohormone (AD diagnosis, left entorhinal cortex atrophy, and left hippocampus atrophy), clusterin (rate of cognitive decline), and fetuin B (left entorhinal atrophy). Multivariate analysis found that a subset of 13 proteins predicted AD with an accuracy of area under the curve of 0.70. Our replication of previous findings provides further evidence that levels of these proteins in plasma are truly associated with AD. The newly identified proteins could be potential biomarkers and are worthy of further investigation.